Peran Lembaga Perlindungan Saksi dan Korban dalam Putusan Pengadilan Terhadap Anak yang Menjadi Korban Kejahatan Seksual - Allena Marvelia Silalahi; Boedi Prasetyo (Dinasti Research, 2025)
This study aims to find out the important role of the Witness and Victim Protection Institution (LPSK) in the judicial system in Indonesia. This assessment was carried out by reviewing various relevant regulations, such as Law Number 35 of 2014 and Number 11 of 2012. This study found that LPSK has a crucial function in providing comprehensive protection to victims' children. The protection includes assistance in legal proceedings as well as efforts to recover physical and psychological conditions. The results of this study emphasize the significance of LPSK's role in ensuring that children who are victims of sexual violence receive appropriate justice and protection.